Pengaruh Sanksi Perpajakkan dan Pengetahuan Perpajakkan terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor pada Samsat Kota Solok - Juita Sukraini; Lili Wahyuni; Zihan Riska Muzida (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This research was conducted to determine the Effect of Tax Sanctions and Tax Knowledge on Motor Vehicle Taxpayer Compliance. The population in this research consists of motor vehicle taxpayers registered at the SAMSAT Office of Solok City from 2021 to 2024. The sampling technique used in this research is Convenience Sampling. To determine the sample size, the researcher applied Slovin's formula, resulting in 100 respondents. The data analysis method employed SPSS version 26. The research results indicate that the Tax Sanctions variable (X1) has no significant effect on Taxpayer Compliance (Y), as evidenced by the t-count value of 0.933 ≤ 1.9848 (t-table) and a significance value of 0.150 ≥ 0.05 significance level. The Tax Knowledge variable (X2) has a significant effect on Taxpayer Compliance (Y), as evidenced by the t-count value of 2.432 ≥ 1.9848 (t-table) and a significance value of 0.017 ≤ 0.05 significance level. The Tax Sanctions variable (X1) and Tax Knowledge variable (X2) simultaneously have a significant effect on Taxpayer Compliance (Y), as evidenced by the F-count value of 2.846 ≥ 2.70 (F-table) and a significance value of 0.042 ≤ 0.05.